COUP-TFII regulates tumor growth and metastasis by modulating tumor angiogenesis - Qin, Jun (National Academy of Sciences, 2010)
Tumor growth depends on nutrients and oxygen supplied by the vasculature through angiogenesis. Here, we show that the chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII), a member of the nuclear receptor family, is a major angiogenesis regulator within the tumor microenvironment. Conditional ablation of COUP-TFII in adults severely compromised neoangiogenesis and suppressed tumor growth in xenograft mouse models. In addition, tumor growth and tumor metastasis were also impaired in a spontaneous mammary-gland tumor model in the absence of COUP-TFII. We showed that COUP-TFII directly regulates the transcription of Angiopoietin-1 in pericytes to enhance neoangiogenesis. Importantly, provision of Angiopoietin-1 partially restores the angiogenic defects exhibited by the COUP-TFII–deficient mice, which supports the notion that COUP-TFII controls Angiopoietin-1/Tie2 signaling to regulate tumor angiogenesis. Because COUP-TFII has little impact on normal adult physiological function, our results raise an interesting possibility that inhibition of COUP-TFII may offer a therapeutic approach for anticancer intervention.